How Does Starbucks Develop Brand Loyalty Among Its Customers in Asia? Insights From Malaysia, Indonesia, and India - Thiam Yong Kuek; Rosmelisa Yusof; Sushmithaa A/P Selvam; Siti Ramizah Binti Roslan; Son Rakh A/L Aibau; Isha Vats; Jahnavi Singhal; Khushi Chaudhary; Daisy Mui Hung Kee; Xinyi Su (AIBPM Publisher, 2023)
Starbucks' brand loyalty is influenced by several aspects, including pricing, products offered, product quality and taste. The purpose of this research is to determine how Starbucks develops brand loyalty among its customers in Malaysia, India, and Indonesia. This survey will also be able to determine whether Asian customers will continue to be devoted Starbucks customers. The survey involved 136 people who are loyal Starbucks consumers from Malaysia, India, and Indonesia. The data for this study was collected through online sources and questionnaires. The results of this study reveal that customer contentment, the quality of products and services, and the pricing of food and drinks greatly influence customer behavior and their inclination to remain loyal to the Starbucks brand. Among all the independent factors under consideration, customer satisfaction stands out as the most predominant, surpassing the other two variables. It is suggested for Starbucks to prioritize customer satisfaction by consistently exceeding performance and delivering exceptional, diverse beverage options with valuable pricing to meet and exceed customer expectations.